Development Of Inline Rapid Thermal Transient Test System For Crack Detection Of Alingap On Germanium Carrier - Annaniah, Luruthudass (2018)
LEDs are the ultimate light source in the lighting technology and growing at double digit percentage for the past few decades. Despite of many virtues in LEDs, there are many challenges it have. One of it is die crack. In this work, the focus is on die-crack on die substrate of an AlInGaP LED at die attach (DA) process. Here the impact on electro-optical and thermal properties were investigated and a detection method was invented. The cracks were artificially created at Ge substrate using industrial grade DA equipment at bond force range from 40gF to 210gF. Die-crack length were measured using high magnification scope.